Importance of nutritional assessment tools in the critically ill patient: A systematic review - Domenech-Briz, Vicente; Gea-Caballero, Vicente; Czapla, Michal; Chover-Sierra, Elena; Juárez-Vela, Raúl; Santolalla Arnedo, Ivan; Villanueva-Blasco, Víctor J.; Sánchez-González, Juan Luis; Martínez-Sabater, Antonio (Frontiers in Nutrition, 2023)
Background: Among the risks of the critically ill patient, one of the aspects to be taken into account is the high probability of occurrence of malnutrition risk (40-50%). This process leads to increased morbimortality and worsening. The use of assessment tools allows the individualization of care. Objective: to analyze the different nutritional assessment tools used during the admission of critically ill patients. Methods: Systematic review of the scientific literature related to the nutritional assessment of critically ill patients. Between January 2017 and February 2022, articles were rescued from the electronic databases "Pubmed", "Scopus", "CINAHL" and "The Cochrane Library"; which will analyze which instruments are used during nutritional assessment in the ICU, as well as their impact on mortality and comorbidity of patients Results: The systematic review was made up of 14 scientific articles that met the selection criteria, obtained from 7 different countries. The instruments described were: mNUTRIC, NRS 2002, NUTRIC, SGA, MUST and the ASPEN and ASPEN criteria. All the included studies demonstrated beneficial effects after nutritional risk assessment. mNUTRIC was the most widely used assessment instrument, with the best predictive validity for mortality and adverse outcomes Conclusion: The use of nutritional assessment tools makes it possible to know the real situation of patients, and by objectifying situations, to allow different interventions to improve the nutritional level of patients. The best effectiveness has been achieved using tools such as mNUTRIC, NRS 2002 and SGA.